Croxall-Morris family papers - Carroll, Richard, active 1794.; Croxall, Charles; Croxall, Daniel; Croxall, Mary Morris; Croxall, Thomas; Morris, Gouverneur, 1752-1816.; Morris, Robert, 1734-1806.
Correspondence, legal and business papers, genealogical notes, printed matter, and other papers of various members of the Croxall and Morris families, including Richard Carroll, Charles Croxall, Daniel Croxall, Mary Morris Croxall, Thomas Croxall, Gouverneur Morris, and Robert Morris. Also includes information on the allied Wilmer and Carroll families.
Microfilm edition available
Microfilm produced from originals in the Manuscript Division.
Collection material in English.
Keywords: Carroll family; Croxall family; Morris family; Wilmer family